Climate-smart cocoa in forest landscapes: Lessons from institutional innovations in Ghana - van der Haar, S.; Gallagher, E.; Schoneveld, G.; Slingerland, M.; Leeuwis, C. (Elsevier, 2023)
Integrated landscape approaches have been welcomed by scientists and development practitioners as a promising way to address commodity-driven deforestation and associated land degradation and greenhouse gas emissions. They present cross-sectoral approaches to manage trade-offs between multiple land uses and environmental and socio-economic objectives through participatory multi-stakeholder planning and negotiation processes. The success of landscape approaches depends on the larger institutional systems of rules, regulations, and actor networks in which they are embedded. Yet, there remains a critical gap in our understanding of how such enabling conditions can be established. Taking the case of Ghana, this research analyses cross-sectoral institutional innovation in commodity and forestry regimes promoting the enabling conditions to move integrated landscape approaches from theory to practice. As part of its National REDD+ Strategy, Ghana has led the way for jurisdictional REDD+ and has successfully mobilized broad-based stakeholder engagement and funding around a shared purpose: climate-smart cocoa in community co-managed forest landscapes. In this article, we apply a Multi-Level Perspective (Geels, 2002) to analyse the process of institutional innovation under the Ghana Cocoa Forest REDD+ Programme (GCFRP). Despite early signs of regime change and alignment in Ghana’s cocoa and forestry sectors, GCFRP’s success is threatened by, amongst others, frustrated reforms to tree tenure and timber benefit-sharing rights. Our research demonstrates that political commitment for institutional change beyond landscape and jurisdictional scales is essential to enable climate-smart landscape transitions.